Avaliação do volume da cavidade nasal por rinometria acústica, pré e pós-cirurgia endoscópica funcional dos seios paranasais - Santos, Rodrigo de Paula [UNIFESP] (2006)
Acoustic rhinometry is an objective method to determine nasal cavity geometry. The technique is based on sound wave reflexion analysis in the nasal cavity, and determines crossectional areas as a function of distance as well as volume. AIM: The purpose of this study is to analyse nasal cavity volume changes caused by functional endoscopic sinus surgery (FESS) in adults with chronic rhinosinusitis by acoustic rhinometry, and to correlate these changes with improvements in the sensation of nasal obstruction. MATERIAL AND METHOD: Forty patients aged from 18 to 73 years were prospectively evaluated between August and October 1999 at the Graz University Hospital, Austria. All patients were diagnosed with chronic rhinosinusitis, and undertook acoustic rhinometry before and after FESS. SCIENTIFIC DESIGN: A clinical prospective study. RESULTS: The nasal cavity total volume increased significantly after surgery. Nasal obstruction was improved in 88% of the patients, 20% with partial improvement and 68% with total improvement. There was no correlation between volume increase and improvement of the sensation of nasal obstruction. CONCLUSION: Total nasal cavity volume significantly increased after surgery; however, there was no correlation between volume increase and improvements of nasal obstruction. No significant pre or postoperative increase in total nasal cavity volume after decongestion were observed.